The role of demographic variables as the moderator between organizational variables and job stress among teachers in Sabah / Najihah Hanisah Marmaya and Syed Azizi Wafa - Marmaya, Najihah Hanisah; Wafa, Syed Azizi (Research Management Institute (RMI), 2009)
A nationwide investigation into stress among teachers in the United Kingdom, found teachers to be reporting stress-related problems which were far higher than those of the population norms and other comparable occupational groups. Job stress can be influenced by personal factors (Matteson & Ivancevich, 1999). The present study examined the role of demographic variables as the moderator between organizational variables and job stress. A sample size of 177 teachers participated in this study revealed that teachers in Tawau and Lahad Datu experienced low stress levels. This study found that demographic variables do not serve as the moderator between organizational variables and job stress.